Advanced Design for High-Performance and AI Chips - Ying Cao; Yuejiao Chen; Xi Fan; Hong Fu; Bingang Xu (Nano-Micro Letters)
Highlights A comprehensive review focused on the recent advancement of the advanced and artificial intelligence (AI) chip is presented. The design tactics for the enhanced and AI chips can be conducted from a diversity of aspects, with materials, circuit, architecture, and packaging technique taken into considerations, for the pursuit of multimodal data processing abilities, robust reconfigurability, high energy efficiency, and enhanced computing power. A broad outlook on the future considerations of the advanced chip is put forward.